National and international research collaboration network in South Korea: An analysis of library and information science journals (2015–2024) - Byungkyu Kim,; You Beom-Jong,; Shim Hyoung-Seop,; Kang Jihoon, (Malaysian Journal of Library and Information Science, 2025)
This study analyses the structure and collaboration patterns of co-authorship networks in library and information science (LIS) journals published in South Korea and internationally from 2015 to 2024. South Korean journals were categorised into Korean-language and English-language publications, while international journals included all articles and a subset article authored by Korean researchers. This classification enabled a comparative analysis of the structures of collaboration and the impact of co-authorship. The results show that international journals have more authors per article and higher research collaboration than South Korean journals. Among the international journals, articles by Korean researchers showed a high degree of international co-authorship, indicating a growing trend towards global collaboration. Korean journals had more single-authored articles and collaborations within the same institution, with limited international participation. An analysis of the impact of co-authorship on the number of citations found that articles involving collaborations across multiple institutions and disciplines tended to receive more citations. An analysis of the Simpson Diversity Index (SDI) demonstrated higher interdisciplinary diversity in international journals with Korean authors than in Korean journals, reflecting broader academic engagement. A correlation analysis of institutional productivity rankings between Korean and international journals found no significant relationship, suggesting different patterns of collaboration. These findings emphasise the need to expand international co-authorship and promote interdisciplinary collaboration in Korean LIS research. Building a more open and inclusive research environment in Korean journals is crucial to attract diverse authors. This study provides a basic insight into the trends of co-authorship and offers strategies to improve the international visibility and impact of Korean LIS research.